Qijiao moxibustion based on midnight-noon ebb-flow combined with five-element music therapy and nursing management of diarrhea in a patient with hemorrhagic stroke of Qi-deficiency and blood stasis syndrome (子午流注择时气交灸联合五行音乐治疗1例出血性中风气虚血瘀型患者泄泻的护理体会) - LEI Xiaoyang (雷啸阳); CHEN Qing (陈青); XU Shilai (许时来); ZHANG Zhanwei (张占伟); ZHANG Qian (张茜); DENG Haixia (邓海霞) (Association of Integrative Nursing, 2023)
This paper summarized the Qijiao moxibustion based in midnight-noon ebb-flow combined with five-element music therapy and nursing management of diarrhea in a patient with hemorrhagic stroke of Qi-deficiency and blood stasis syndrome. Based on the scientific nursing assessment and Traditional Chinese Medicine theory of midnight-noon ebb-flow, Qijiao moxibustion combined with five-element music therapy was carried out to relieve the diarrhea and improve the recovery of the patient. (本文总结1例子午流注择时气交灸联合五行音乐改善出血性中风气虚血瘀型患者泄泻的护理经验。通过科学的护理评估, 明确护理目标, 在常规护理的基础上遵循子午流注理论实施气交灸联合五行音乐中医护理干预, 改善患者腹泻, 促进康复。)